Methods for the detection of plant viruse diseases - Naidu, R.; Hughes, J. (2003)
Plant viruses cause major losses to several agricultural and horticultural crops around the world. Unlike other plant pathogens, there are no direct methods available yet to control viruses and, consequently, the current measures rely on indirect tactics to manage the viral diseases. Hence, methods for detection and identifi cation of viruses, both in plants and vectors, play a critical role in virus disease management. Diagnostic techniques for viruses fall into two broad categories: biological properties related to the interaction of the virus with its host and/or vector (e.g., symptomatology and transmission tests) and intrinsic properties of the virus itself (coat protein and nucleic acid). Detection methods based on coat protein include precipitation/agglutination tests, enzyme-linked immunosorbent assays, and immunoblotting. Viral nucleic acid-based techniques like dot-blot hybridization assays and polymerase chain reaction are more sensitive than other methods. Availability of these diagnostic methods provides greater fl exibility, increased sensitivity, and specifi city for rapid diagnosis of virus diseases in disease surveys, epidemiological studies, plant quarantine and seed certifi cation, and breeding programs. Nevertheless, deployment and effective utilization of these techniques and diagnostic reagents (viz. antibodies and kits) to address plant virus disease problems in sub-Saharan Africa depends on having minimum research facilities and critical scientific expertise in the national agricultural research systems. Thus, programs to improve knowledge in plant virology and strengthen skills for virus diagnosis are vital for crop improvement and agricultural sustainability in the region.